Electrophysiological Evidence of Enhanced Processing of Novel Pornographic Images in Individuals With Tendencies Toward Problematic Internet Pornography Use - Wang, Jianfeng; Chen, Yuanyuan; Zhang, Hui (Frontiers in Human Neuroscience, 2022)
Novelty seeking is regarded as a core feature in substance use disorders. However, few studies thus far have investigated this feature in problematic Internet pornography use (PIPU). The main aim of the present study was to examine group differences in electrophysiological activity associated with novelty processing in participants with high tendencies toward PIPU vs. low tendencies using event-related potentials (ERPs). Twenty-seven participants with high tendencies toward PIPU and 25 with low tendencies toward PIPU completed a modified three-stimulus oddball task while electroencephalogram (EEG) was recorded. Participants were instructed to detect neutral target stimuli from distracting stimuli. The distracting stimuli contained a familiar sexual stimulus and a set of novel sexual stimuli. The novel-familiar difference waves were calculated to identify specific group difference in novelty effect. While both groups demonstrated a sustained novelty effect in the late positive potential (LPP) within the 500–800 ms time windows, the novelty effect was greater in the high tendencies toward PIPU group than in the low tendencies toward PIPU group. This result suggests that individuals with high tendencies toward PIPU allocate more attentional resources for novelty processing. Enhanced brain responding to novel sexual stimuli may facilitate pornographic consumption and play an essential role in the development and maintenance of PIPU.